2021
DOI: 10.3389/fpsyt.2021.632784
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-Up Study of Boys With Gender Identity Disorder

Abstract: This study reports follow-up data on the largest sample to date of boys clinic-referred for gender dysphoria (n = 139) with regard to gender identity and sexual orientation. In childhood, the boys were assessed at a mean age of 7.49 years (range, 3.33–12.99) at a mean year of 1989 and followed-up at a mean age of 20.58 years (range, 13.07–39.15) at a mean year of 2002. In childhood, 88 (63.3%) of the boys met the DSM-III, III-R, or IV criteria for gender identity disorder; the remaining 51 (36.7%) boys were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 122 publications
0
38
0
3
Order By: Relevance
“…This research adds to the existing evidence that gender dysphoria can be temporary (Ristori & Steensma, 2016;Singh et al, 2021;Zucker, 2018). It has been established that the most likely outcome for prepubertal youth with gender dysphoria is to develop into lesbian, gay, bisexual (LGB) (non-transgender) adults (Ristori & Steensma, 2016;Singh et al, 2021;Wallien & Cohen-Kettenis, 2008;Zucker, 2018). And, temporary gender dysphoria may be a common part of LGB identity development (Korte et al, 2008;Patterson, 2018).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This research adds to the existing evidence that gender dysphoria can be temporary (Ristori & Steensma, 2016;Singh et al, 2021;Zucker, 2018). It has been established that the most likely outcome for prepubertal youth with gender dysphoria is to develop into lesbian, gay, bisexual (LGB) (non-transgender) adults (Ristori & Steensma, 2016;Singh et al, 2021;Wallien & Cohen-Kettenis, 2008;Zucker, 2018). And, temporary gender dysphoria may be a common part of LGB identity development (Korte et al, 2008;Patterson, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…For these individuals, exploring their distress and discomfort around sexual orientation issues may have been more helpful to them than medical and surgical transition or at least an important part of exploration before making the decision to transition. This research adds to the existing evidence that gender dysphoria can be temporary (Ristori & Steensma, 2016;Singh et al, 2021;Zucker, 2018). It has been established that the most likely outcome for prepubertal youth with gender dysphoria is to develop into lesbian, gay, bisexual (LGB) (non-transgender) adults (Ristori & Steensma, 2016;Singh et al, 2021;Wallien & Cohen-Kettenis, 2008;Zucker, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…This pattern was observed even though there are no agreed-on standards or measures to determine whether to support a given child through a social transition. Past work has linked extremity of gender nonconformity in the absence of early social transitions to transgender identification later in life (e.g., Singh, 2012; Steensma et al, 2013; Wallien & Cohen-Kettenis, 2008), so these findings could suggest that the children transitioning at early ages may also be more likely to identify as transgender later in life. Critically, these results were robust to a large number of analytic decisions (e.g., inclusion of covariates or using different prior distributions for our Bayesian analyses) and data-processing decisions (e.g., how we combined the five gender-development measures or handled missing data).…”
Section: Discussionmentioning
confidence: 99%
“…Past longitudinal work has found that gender-nonconforming children who identify as transgender in adolescence and adulthood tended to show more extreme childhood gender nonconformity than gender-nonconforming children who did not later identify as transgender (Singh, 2012; Steensma et al, 2013; Wallien & Cohen-Kettenis, 2008). Most or all participants in these studies had not completed a full social transition as prepubescent children (i.e., had not changed pronouns), as social transitions are a fairly recent practice.…”
mentioning
confidence: 99%
“…Second, the evidence supporting their effectiveness in the treatment of GD is extremely poor (NICE 2020). Third, most young people spontaneously desist from their trans identification if left untreated (Cantor 2017;Singh, Bradley & Zucker 2021), while almost 100% given puberty blockers proceed to further medical treatment (Judicial Review 2020: Bell v. The Tavistock & Portman NHS Foundation Trust). Fourth, as outlined in the recent judicial review (ibid.…”
mentioning
confidence: 99%